2015
DOI: 10.1186/s12889-015-2315-z
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community level determinants of childhood full immunization in Ethiopia: a multilevel analysis

Abstract: BackgroundExpanded program on immunization is one of the most successful and cost effective public health interventions that protect children against vaccine preventable diseases. The full childhood immunization coverage in many parts of Ethiopia is far from optimal. Hence, the main objective of this study was to assess factors associated with childhood full immunization in Ethiopia.MethodsThe data source for this study was the 2011 Ethiopian Demographic and Health Survey. Multilevel regression analysis techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
107
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 32 publications
45
107
3
2
Order By: Relevance
“…Maternal education was associated with improved vaccination coverage in this study and similar findings have been described for Ethiopia, in multi-country assessments of inequities in vaccination coverage, and in systematic reviews of studies from 13 and 51 countries [9,23,26-30]. A higher maternal educational level raises awareness about the importance of vaccination and it has been reported that educated women choose health care services that generate better health [27,31].…”
Section: Maternal Educationsupporting
confidence: 85%
“…Maternal education was associated with improved vaccination coverage in this study and similar findings have been described for Ethiopia, in multi-country assessments of inequities in vaccination coverage, and in systematic reviews of studies from 13 and 51 countries [9,23,26-30]. A higher maternal educational level raises awareness about the importance of vaccination and it has been reported that educated women choose health care services that generate better health [27,31].…”
Section: Maternal Educationsupporting
confidence: 85%
“…Abadura et al (2015) stated that exposure of information media also influences children's complete basic immunization status. Family who is exposed to media (the utilization of television or radio once in a week at the minimum) has higher possibility to complete their children immunization compares to family who are less exposed to media.…”
Section: Resultsmentioning
confidence: 99%
“…These unpleasant experience definitely affected the mother's intention and the practice of vaccination, leading to the missed opportunities or the drop outs of vaccination. 24,25 We suggested that all vaccination providers adjust the vaccination session and extend the working hours to reduce the vaccine hesitancy among mothers, which had been indicated to be effective among migrant population in Zhejiang province and might be the most beneficial to the working mothers. As in our study, previous reports had shown that the parents' information searches on vaccination were positively associated with their intention to vaccination.…”
Section: Discussionmentioning
confidence: 99%